Ursodeoxycholic acid inhibits uptake and vasoconstrictor effects of taurocholate in human placenta. Issue 7 (28th March 2019) - Lofthouse, Emma M.; Torrens, Christopher; Manousopoulou, Antigoni; Nahar, Monica; Cleal, Jane K.; O'Kelly, M. Ita; Sengers, Bram G.; Garbis, Spiros D.; Lewis, Rohan M.
ABSTRACT: Intrahepatic cholestasis of pregnancy (ICP) causes increased transfer of maternal bile acids to the fetus and an increased incidence of sudden fetal death. Treatment includes ursodeoxycholic acid (UDCA), but it is not clear if UDCA protects the fetus. This study explores the placental transport of the bile acid taurocholate (TC) by the organic anion–transporting polypeptide, (OATP)4A1, its effects on the placental proteome and vascular function, and how these are modified by UDCA. Various methodological approaches including placental villous fragments and Xenopus laevis oocytes were used to investigate UDCA transport. Placental perfusions and myography investigated the effect of TC on vasculature. The effects of acute TC exposure on placental tissue were investigated using quantitative proteomics. UDCA inhibited OATP4A1 activity in placental villous fragments and oocytes. TC induced vasoconstriction in placental and rat vasculature, which was attenuated by UDCA. Quantitative proteomic analysis of villous fragments showed direct effects of TC on multiple placental pathways, including oxidative stress and autophagy. The effects of TC on the placental proteome and vasculature demonstrate how bile acids may cause fetal distress in ICP. UDCA inhibition of OATP4A1 suggests it will protect the mother and fetus against the vascular effects of TC by inhibiting its cellular uptake. UDCA may protect the fetus in ICP by inhibiting OATP4A1‐mediated bile acid transfer and TC‐induced placental vasoconstriction. Understanding the physiologic mechanisms of UDCA may allow better therapeutic interventions to be designed specifically for the fetus in the future.—Lofthouse, E. M., Torrens, C., Manousopoulou, A., Nahar, M., Cleal, J. K., O'Kelly, I. M., Sengers, B. G., Garbis, S. D., Lewis, R. M. Ursodeoxycholic acid inhibits uptake and vasoconstrictor effects of taurocholate in human placenta. FASEB J. 33, 8211–8220 (2019). www.fasebj.org